Discriminatory, yet socially accepted? Targets’ perceptions of subtle and blatant expressions of ethno-racial prejudice - Stanke, Franziska A.; Kuper, Niclas; Fetz, Karolina; Echterhoff, Gerald (Frontiers in Social Psychology, 2024)
Extant research has studied prejudice expressions mainly from the majority perspective. We examined whether prejudice expressions conceptualized as subtle (vs. blatant) are perceived differently by their targets. Participants who self-identified as potential targets of ethno-racial or religious prejudice (e.g., anti-Muslim, anti-Asian, anti-Arab, anti-Slavic, and anti-Black prejudice), answered questions about verbal expressions of prejudice taken from the subtle and blatant prejudice scales (Pettigrew & Meertens, 1995) in an online survey. Items of the subtle (vs. blatant) prejudice scale were rated as more socially accepted and less discriminatory, elicited less negative emotions, and were reported to be experienced more often. Subtle expressions of prejudice were not more familiar to participants than blatant ones. Remarkably, blatant prejudice expressions were also perceived as relatively socially accepted and subtle prejudices as relatively discriminatory, as indicated by mean ratings above the scale midpoint. Lower discrimination ratings of subtle (vs. blatant) prejudice expressions were mainly due to perceptions of expressions exaggerating cultural differences. We discuss implications for interventions, especially regarding the social acceptability of blatant prejudice and promoting awareness of the discriminatory impact of subtle prejudice.